2018
DOI: 10.1104/pp.18.00715
|View full text |Cite
|
Sign up to set email alerts
|

The Ring-Type E3 Ubiquitin Ligase JUL1 Targets the VQ-Motif Protein JAV1 to Coordinate Jasmonate Signaling

Abstract: Jasmonates regulate plant defense and development. In Arabidopsis (Arabidopsis thaliana), JASMONATE-ASSOCIATED VQ-MOTIF GENE1 (JAV1/VQ22) is a repressor of jasmonate-mediated defense responses and is degraded through the ubiquitin-26S proteasome system after herbivory. We found that JAV1-ASSOCIATED UBIQUITIN LIGASE1 (JUL1), a RING-type E3 ubiquitin ligase, interacted with JAV1. JUL1 interacted with JAV1 in the nucleus to ubiquitinate JAV1, leading to proteasomal degradation of JAV1. The transcript levels of JU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 64 publications
4
45
1
Order By: Relevance
“…A homology search of The Arabidopsis Information Resource (http://www.arabidopsis.org) database revealed that At5g10650 is identical to JUL1 (Ali et al, 2019). JUL1 is a nuclear-localized RING E3 ligase that was recently reported to ubiquitinate and induce the 26S proteasomedependent degradation of JASMONATE-ASSOCIATED VQ-MOTIF GENE1 (JAV1/VQ22), a repressor of jasmonatemediated defense response to herbivory.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A homology search of The Arabidopsis Information Resource (http://www.arabidopsis.org) database revealed that At5g10650 is identical to JUL1 (Ali et al, 2019). JUL1 is a nuclear-localized RING E3 ligase that was recently reported to ubiquitinate and induce the 26S proteasomedependent degradation of JASMONATE-ASSOCIATED VQ-MOTIF GENE1 (JAV1/VQ22), a repressor of jasmonatemediated defense response to herbivory.…”
Section: Resultsmentioning
confidence: 99%
“…At5g10650 was colocalized to microtubules and microtubule-associated proteins (MAPs) in Arabidopsis and tobacco leaf cells. Unexpectedly, At5g10650 was found to be identical to the nuclear-localized JAV1-ASSO-CIATED UBIQUITIN LIGASE1 (JUL1), which is involved in jasmonate signaling after herbivory (Ali et al, 2019). The jul1 knockout progeny exhibited impaired stomatal closure in response ABA, H 2 O 2 , and CaCl 2 , suggesting that JUL1 is downstream of ROS and calcium in the ABA-promoted stomatal closure pathway.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the mitogen-activated protein (MAP) kinase 3/6-targeted VQ protein 1 (MVQ1, also known as AtVQ4) plays a negative role in regulating pathogen-associated molecular pattern (PAMP)-induced resistance to pathogens [27]; AtVQ9 negatively regulates salinity stress responses [28]; HAIKU1 (IKU1, also known as AtVQ14) exhibits an essential role in the determination of Arabidopsis seed size through the IKU pathway [29]; AtCaMBP25/AtVQ15 functions as a negative effector of osmotic stress tolerance during seed germination and seedling growth [30]; AtVQ20 acts as a key player to modulate pollen development, germination, and tube growth [31]; MKS1/AtVQ21 contributes to the MAP kinase 4 (MPK4)-activated pathogen defense and the overexpression of AtVQ21/MKS1 resulted in increased tolerance to Pseudomonas syringae pv. tomato in transgenic Petunia plants [32][33][34]; jasmonate-associated VQ motif protein 1 (JAV1, also known as AtVQ22) acts as a repressor protein in JA-mediated defense responses against necrotrophic pathogens and herbivorous insects without influencing plant growth and development [35,36]; SIB1/AtVQ23 and SIB2/AtVQ16 function as activators in plant defense against necrotrophic pathogens [37]. Additionally, AtVQ18 and AtVQ26 were found to fine-tune seed germination and seedling establishment [38], while AtVQ29 was reported to interact with Phytochrome-Interacting Factor 1 (PIF1), leading to the repression of seedling de-etiolation [39].…”
Section: Introductionmentioning
confidence: 99%
“…3). In jasmonate signaling, an array of signal components which fine-tune plant sensitivity to the hormone, e.g., JAZ (JASMONATE-ZIM DOMAIN) repressors, JAV1 (JASMONATE-ASSOCIATED VQ-MOTIF GENE 1) and JUL1 (JAV1-ASSOCIATED UBIQUITIN LIGASE 1), function downstream of jasmonate biosynthesis in the model Arabidopsis plant [30][31][32] . Similarly, a suite of ethylene signaling factors such as ethylene receptors (e.g., ETR1), a protein kinase (CTR1), The net body weight that Spodoptera litura larvae gained during 2 days or 4 days after they had been placed on potted plants of WT or transgenic lines (VC or SaERF-expressing plants [ERF1-OX1, ERF2-OX2, ERF-OX2, and ERF-OX3]).…”
Section: Discussionmentioning
confidence: 99%